Large dentigerous cyst in the maxillary sinus causing bone erosion of the sinus walls - Disher, Mohanned A.; Ali, Amjed H.; Beden, Imad G. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Dentigerous cyst is a type of odontogenic cysts occurs in the ages of twenties or thirties and rarely occurs in the first decade of life with male predominance.  In this report, a case of a large dentigerous cyst in 34 years old female patient   complaining from progressive painful swelling of the right cheek for a month duration. CT scan of the paranasal sinuses showed a well-defined solitary expansile right maxillary cystic mass eroding the antero-lateral maxilla, with a crown of a tooth projecting inside the cystic cavity.  The dentigerous cyst totally enucleated through sublabial incision in combination with nasal endoscopic approach. The unerupted tooth removed from inside the right maxillary antrum. Follow-up at 2 weeks showed no abnormality at the surgical site and no any paresthesia.